DAMPAK SAHAM BONUS PADA NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Baskara, Ida Bagus Putu Puja; Astika, Putra (E-Jurnal Akuntansi; Vol 19 No 2 (2017), 2017)
This study aimed to obtain empirical evidence a difference in value of the company before and after the bonus shares and the influence of the amount of bonus shares distributed to the value of the company after bonus shares. This study was peformed on companies go public listed in the Indonesia Stock Exchange (BEI) and the bonus shares 2000-2015. The number of samples are 44 samples obtained by the method nonprobability sampling purposive sampling technique. The analysis technique used in this research is the difference and simple regression analysis. The analysis showed that the difference in value of the company before and after the bonus shares. This shows that the market provide different response to the bonus shares. The number of bonus shares has positive influence on the value of the company after the bonus shares. This picture proves that the difference is caused by the market reaction bonus shares.
Keywords: Bonus Shares, The Value of the Company